2003
DOI: 10.1093/jn/133.6.1978s
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Influences: Factors Influencing a Woman's Decision to Use Dietary Supplements

Abstract: Use of dietary supplements by women, particularly those over 40 years of age may be widespread in the United Kingdom. However, from surveillance data, there appears to be a disparity between nutrition and health needs and the rationale for and actual use of dietary supplements by women. This apparent paradox forms the basis for an inverse supplement hypothesis (i.e., supplement use in women appears to be most prevalent among those with least need). Little research has been done to examine the factors underlyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 6 publications
6
53
0
1
Order By: Relevance
“…diseases or to treat existing conditions (5,49,52) . Although participants in The Tomorrow Project were asked about previous diagnoses of chronic conditions, we could not ascertain whether those who indicated that they had ever received such a diagnosis still had that condition.…”
Section: Discussionmentioning
confidence: 99%
“…diseases or to treat existing conditions (5,49,52) . Although participants in The Tomorrow Project were asked about previous diagnoses of chronic conditions, we could not ascertain whether those who indicated that they had ever received such a diagnosis still had that condition.…”
Section: Discussionmentioning
confidence: 99%
“…The TPB has been employed in research predicting health behaviours such as parent's immunization intentions [21], diet [22], and exercise [23]. Support for the TPB has been demonstrated in several meta-analyses including Godin and Kok's [24] research.…”
Section: The Theory Of Planned Behaviourmentioning
confidence: 99%
“…It has been implied that a higher education level gives a greater awareness of the role of nutrition in good health. 24,25 Few studies have examined the effects of micronutrient supplementation on long-term child health outcomes, such as child mortality, morbidity, growth and cognitive development. A large trial in Indonesia showed that prenatal micronutrient supplementation was associated with a significant 18% reduction in early infant mortality.…”
Section: Discussionmentioning
confidence: 99%